Kaempferol Attenuates Myocardial Ischemic Injury via Inhibition of MAPK Signaling Pathway in Experimental Model of Myocardial Ischemia-Reperfusion Injury. (21st March 2016) - Suchal, Kapil; Malik, Salma; Gamad, Nanda; Malhotra, Rajiv Kumar; Goyal, Sameer N.; Chaudhary, Uma; Bhatia, Jagriti; Ojha, Shreesh; Arya, Dharamvir Singh
Abstract : Kaempferol (KMP), a dietary flavonoid, has antioxidant, anti-inflammatory, and antiapoptotic effects. Hence, we investigated the effect of KMP in ischemia-reperfusion (IR) model of myocardial injury in rats. We studied male albino Wistar rats that were divided into sham, IR-control, KMP-20 + IR, and KMP 20 per se groups. KMP (20 mg/kg; i.p.) was administered daily to rats for the period of 15 days, and, on the 15th day, ischemia was produced by one-stage ligation of left anterior descending coronary artery for 45 min followed by reperfusion for 60 min. After completion of surgery, rats were sacrificed; heart was removed and processed for biochemical, morphological, and molecular studies. KMP pretreatment significantly ameliorated IR injury by maintaining cardiac function, normalizing oxidative stress, and preserving morphological alterations. Furthermore, there was a decrease in the level of inflammatory markers (TNF- α, IL-6, and NF κ B), inhibition of active JNK and p38 proteins, and activation of ERK1/ERK2, a prosurvival kinase. Additionally, it also attenuated apoptosis by reducing the expression of proapoptotic proteins (Bax and Caspase-3), TUNEL positive cells, and increased level of antiapoptotic proteins (Bcl-2). In conclusion, KMP protected against IR injury by attenuating inflammation and apoptosis through the modulation of MAPK pathway.